Enhancing video-based learning experience through smart environments and analytics - Giannakos, M.; Sampson, Demetrios; Kidzinski, L.; Pardo, A. (2016)
This paper describes the potential and promising value of smart environments and analytics on the emerging area of video-based learning. In particular, we describe the contributions presented at the International Workshop of Smart Environments and Analytics on Video-Based Learning (SE@VBL) and envision the future of this research area. SE@VBL presents the current state-of-the- art in the design, development and evaluation of video-based learning systems. SE@VBL 2016 emphasized the importance and benefits of smart environments and analytics for video-based learning to support learners and instructors with the appropriate resources for improving the use of video-based learning systems. The long term goal of SE@VBL is to develop a critical discussion about the next generation of environments and analytics employed in video learning tools, the form of these environments and analytics, and the way they can be utilized in order to help us to better understand and improve the value of video-based learning. In this volume, we have included the 4 contributions, 1 keynote presentation and 1 tutorial that were featured at the workshop.